Pathogen distribution and liver injury severity in children with community-acquired pneumonia complicated by liver injury in Suzhou, China - Wang, Kun; Li, ZhengJiayi; Cheng, Fangfang (Frontiers in Pediatrics, 2025)
BackgroundLiver injury is a extrapulmonary complication of community-acquired pneumonia (CAP). However, limited data exist on the pathogen distribution and severity of liver injury in children with CAP-associated liver injury. This study aimed to investigate the characteristics of pathogen distribution and the severity of liver injury in children with CAP complicated by liver injury in the Suzhou area.MethodsA retrospective study was conducted on children with CAP hospitalized at the Children's Hospital of Soochow University between January 2018 and December 2022. The study included children aged over 28 days to under 18 years, categorized into the following age groups: >28 days to 1 year, >1–3 years, >3–5 years, and >5 years. Laboratory examination results, pathogens, and characteristics of liver injury were analyzed.ResultsAmong the 1525 children with CAP complicated by liver injury, the male-to-female ratio was 1.4:1. Mild elevation of transaminases were observed in 1,403 cases. In the same age group, there were differences in the proportion of cases with varying degrees of liver injury (p < 0.05). Among the four age groups, both the number of cases and the incidence of liver injury were highest in the >28 days to 1-year-old group. The incidence of liver injury was higher in children with severe community-acquired pneumonia (SCAP). Additionally, the distribution of pathogens varied significantly among age groups (p < 0.001). Children with severe liver injury were mostly accompanied by Mycoplasma pneumoniae (M. pneumoniae) infection (88.89%). Alanine aminotransferase (ALT) levels also varied significantly based on age group, pathogen type, and pneumonia severity (p < 0.05). Importantly, none of the children progressed to liver failure.ConclusionsIn the Suzhou area, children with CAP aged >28 days to 1 year were the most susceptible to liver injury, with mild elevation of transaminases being the most common presentation. Special attention was required for children with CAP complicated by M. pneumoniae infection, as they carried a higher risk of severe liver injury. Children with SCAP were more prone to liver injury. Additionally, pathogen distribution varied across different age groups in children with CAP complicated by liver injury.